Design and analysis of 2-coil wireless power transfer (WPT) using magnetic coupling technique - A. Ali; M.N.M Yasin; M.F.C. Husin; N.A.M Ahmad Hambali (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
2-coil non-radiative wireless power transfer (WPT) is studied to find the coil diameter ratio to effective distance of power transfer efficiency (PTE). Single circular coil and spiral coil are designed and simulated using CST software to compare the result of coil diameter versus effective distance of PTE by using S21 value. Accordingly, the quality factor (Q) of both coils are presented as Q factor is one of the parameter that affect the performance of WPT system. The result is promising as the effective distance is more than the coil diameter with (PTE) more than 50% using spiral coil as compare to single coil design.